Soft-Templating Synthesis of Granular Magnetite Nanowires and Their Magnetic Properties - Han, Chengliang; Zhao, Difang; Lu, Hongdian; Ming, Ding (Asian Journal of Chemistry, 2012)
A facile synthesis of granular Fe3O4 nanowires in aqueous mediums is reported. The results showed that the proteins can be used as a soft template for synthesis of Fe3O4 nanowires. The as-prepard Fe3O4 nanowires are made of many magnetite nanoparticles and have excellent magnetic properties (Ms = 81 emu/g, Hc = 145Oe) at room temperature.